Implementasi Pendidikan Inklusif Bagi Anak Autisme - Adeani, Isnaini; Husna, Asmaul; Hijriati, Hijriati (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2025)
This study aims to describe the implementation of inclusive education for children with autism at TK Harsya Ceria. A qualitative approach with descriptive research type was used. The subjects of the study were teachers and parents, while the object was the implementation of inclusive education for autistic children. Data collection techniques included observation, interviews, and documentation. Data analysis used the interactive model of Miles and Huberman, consisting of data reduction, data display, and conclusion drawing. The results showed that TK Harsya Ceria had implemented inclusive education by adapting learning to the specific needs of students, particularly by focusing on sensory stimulation. The school provided an environment that supports the development of children with autism through a flexible, child-centered learning approach. In conclusion, the implementation of inclusive education at TK Harsya Ceria is fairly effective and provides opportunities for children with autism to develop optimally according to their abilities